(untitled) (Contemporary Mathematics, 2024)
We introduce a certain subclass of analytic functions in the open unit disk U involving the q-derivative operator. Some convolution results and Fekete-Szegö inequalities for the analytic functions belonging to this class are derived. We have also provided some results as corollaries of our theorems.